Numerical simulation of surface acoustic wave actuated enantiomer separation by the finite element immersed boundary method. (2nd May 2015) - Beleke-Maxwell, K.; Franke, T.; Hoppe, R.H.W.; Linsenmann, C.
Highlights: We consider the numerical simulation of surface acoustic wave actuated enantiomer separation. The separation mechanism is based on surface acoustic wave generated vorticity patterns. The simulation is done by the finite element immersed boundary method. Abstract: Enantiomers are chiral objects such as chemical molecules that can be distinguished by their handedness. They typically occur as racemic compounds of left- and right-handed species which may have completely different properties. Therefore, in applications such as drug design in pharmacology, enantiomer separation is an important issue. Here, we present a new technology for enantiomer separation by surface acoustic wave generated vorticity patterns consisting of pairwise counter-rotating vortices in a carrier fluid. The enantiomers are injected onto the surface of the fluid between two counter-rotating vortices such that right-handed (left-handed) enantiomers get attracted by left-rotating (right-rotating) vortices. In particular, we are concerned with the numerical simulation of this separation process by an application of the finite element immersed boundary method which relies on the solution of a coupled system consisting of the incompressible Navier–Stokes equations and the equations of motion of the immersed enantiomers described with respect to an Eulerian and a Lagrangian coordinate system. For a model system of deformable, initially L-shaped enantiomers the results of the numerical simulations reveal a perfect separation.